Analysis of Poverty Alleviation Through Family Hope Program (PKH) In Maqashid Sharia Perspective - Muhamad Wildan Fawa’id; Yopi Yudha Utama (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2022)
The Family Hope Program (PKH) is a program for providing conditional social assistance to poor and vulnerable families registered in the integrated data of the poor care program. The Family Hope Program (PKH) in Nganjuk Regency rolled out from 2013 in 20 sub-districts with a total of 55,000 beneficiary families (KPM). This study aims to provide an overview of poverty alleviation through the Family Hope Program (PKH) in Nganjuk Regency, as well as to see the gap in policy recommendations. This research uses qualitative methods with a policy approach including policy formulation, policy implementation and policy implications. This research resulted in several recommendations to social services in poverty alleviation through the Family Hope Program (PKH). First, the spirit in implementing the Family Hope Program (PKH) is valid poverty data, but the validity of poverty data is still homework that has never been completed to this day. Second, there has not been good cooperation between government institutions, even though the Family Hope Program (PKH) is like an orchestra, between one institution and another, in this case the Social Service, Education Office, Health Office, Population and Civil Registry Office, BKKBN, and the Ministry of Villages must synergize with each other. Third, the Family Hope Program (PKH) has goals that are in line with Maqashidu Syariah, but in terms of Hifdzu Diin (Maintaining Religion) it has not been fully implemented by PKH Assistants for various reasons. In conclusion, poverty data can be validated as accurately as possible through the village level with an integrated application. Ideally the state has one intact poverty indicator that can be used for a variety of purposes. The Whole of Government (WOG) needs to be improved for ease of access and acceleration of poverty alleviation.